NUTRIENT POTENTIAL OF Coix Lachryma-Jobi L. AS RUMINANT FEED SOURCE IN EAST KALIMANTAN - Mayulu, Hamdi; Daru, Taufan Purwokusumaning; Suyadi; Christiyanto, Marry (International Journal of Psychosocial Rehabilitation, 2020)
Increasing population and productivity are alternative policies that must be implemented comprehensively in East Kalimantan by applying the concept of feed forage budgeting. Utilization of superior forage through exploration of local resource to find new feed source is a necessity. The objective of this research was to determine the nutrient composition, dry matter digestibility (DMD) and organic matter digestibility (OMD) of Coix lachryma-jobi. This research was conducted at Laboratory of Animal Nutrient Science, Faculty of Animal Science and Agriculture, Diponegoro University, Semarang by using proximate analysis and in vitro method. The result showed that Coix lachryma-jobi contained of MC (13.27%); DM (86.73%); CP (8.10%); EE (0.89%); CF (21.29%) and ash (12.08%). The stem contained of MC (12.95%); DW (87.05%); CP (7.94%); EE (0.96%); CF (24.11%) and ash (11.26%). The bran contained of MC (11.53%); DM (88.47%); CP (12.55%); EE (6.40%); CF (60.78%) and ash (8.74%).The DMD of leaves was 59.56%; OMD of leaves was 38.22%; DMD of stem was 51.77% and OMD of stem was 34.41%. This showed that Coix lacryma-jobi L. is potential to be used for ruminant feed source especially for ration combined with other feed sources through the application of feed processing technology (hay, silage, amofer, complete feed). Effective biomass utilization could provide continue and sustainable feed source thus it can meet the needs of ruminant and give additional economic advantages.